Comparative Study on Heavy Metals Biosorption by Different Types of Bacteria - Gelagutashvili, Eteri (Scientific Research, 2013)
Biosorption of Cd(II), Ag(I) and Au(III) by cyanobacteria Spirulina platensis, of Au(II)—by Streptomyces spp. 19H, and of Cr(VI) and Cr(III)—by Arthrobacter species was studied by using the dialysis and atomic absorption analysis under various conditions. In particular, the impact of the following parameters on biosorption was studied: pH (for Ag, Cd, Au), living and non-living cells (for Cr), heavy metal valence (for Cr), homogenized and non-homogenized cells (for Au), Zn(II) ions (on Cr(VI)—Arthrobacter species). It was shown that biosorption efficiency of Cr(III), Cr(VI), Cd(II), Au(III) and Ag(I) ions is likely to depend on the type of bacteria used as well as on the conditions under which the uptake processes proceeded. It was shown that metal removal by microorganisms was influenced by physicalchemical parameters. The pH value of 7.0 was optimum for the removal of Ag(I) and Cd(II) by Spirulina platensis. At a low pH value of 5.5, Au (III) was by test algae more efficiently than Cd(II) and Ag(I).
Keywords: Biosorption; Heavy Metals; Cyanobacteria; Actinomycetes